Moral self-cultivation East and West: A critique. Issue 2 (2nd April 2016) - Slote, Michael
Abstract: Moral Self-Cultivation plays an important, even a central role, in the Confucian philosophical tradition, but philosophers in the West, most notably Aristotle and Kant, also hold that moral self-cultivation or self-shaping is possible and morally imperative. This paper argues that these traditions are psychologically unrealistic in what they say about the possibilities of moral self-cultivation. We cannot shape ourselves in the substantial and overall ways that Confucianism, Aristotle, and Kant say we can, and our best psychological data on moral education and development indicate strongly that these phenomena depend crucially on the intervention of others and, more generally, on external factors individuals don't control.